PENINGKATAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL KOOPERATIF TIPE TGT DI KELAS V SDN 12 PAGARUYUNG KABUPATEN TANAH DATAR - Miftahul Jannah; Yesi Anita Zuardi; Yeni Erita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the results of observations in the field, namely the low learning outcomes of students due to a lack of learning activities that involve students because the learning process is still centered on the teacher, so that students are still less active in the learning process. This research aims to describe how to improve student learning outcomes in Pancasila education learning by using a Team Games Tournament (TGT) type cooperative model. This type of research is classroom action research (PTK) using qualitative and quantitative approaches. This research was carried out in two cycles, with research procedures consisting of planning, implementation, observation and reflection. The research data obtained is related to the results of the Team Games Tournament type cooperative learning model. Data collection techniques include tests and non-tests. The subjects of this research were class teachers as observers, researchers as practitioners or teachers, and 20 class V students at SDN 12 Pagaruyung, Tanah Datar Regency. The research results showed that the teaching module for cycle I obtained an average of 79.16% (C), increasing in cycle II to 91.66% (A). The results of the implementation of teacher activity learning in cycle I obtained an average of 71.42% (C), increasing in cycle II, namely 92.85% (A). The results of the implementation of learning activities for students in cycle I obtained an average of 71.42% (C), increasing in cycle II to 92.85% (A). Thus, it can be concluded that the Team Games Tournament (TGT) type cooperative model can increase student learning outcomes from 25% to 85% in Pancasila education learning in class V at SDN 12 Pagaruyung, Tanah Datar Regency.